Environmental impact assessment in health technology assessment: principles, approaches, and challenges. (23rd February 2023) - Toolan, Michael; Walpole, Sarah; Shah, Koonal; Kenny, Juliet; Jónsson, Páll; Crabb, Nick; Greaves, Felix
Abstract: To reduce harm to the environment resulting from the production, use, and disposal of health technologies, there are different options for how health technology assessment (HTA) agencies can consider environmental information. We identified four approaches that HTA agencies can use to take environmental information into account in healthcare decision making and the challenges associated with each approach. Republishing data that is in the public domain or has been submitted to an HTA agency we term the "information conduit" approach. Analyzing and presenting environmental data separately from established health economic analyses is described as "parallel evaluation." Integrating environmental impact into HTAs by identifying or creating new methods that allow clinical, financial, and environmental information to be combined in a single quantitative analysis is "integrated evaluation." Finally, evidence synthesis and analysis of health technologies that are not expected to improve health-related outcomes but claim to have relative environmental benefits are termed "environment-focused evaluation."